Food as a transcultural metaphor food imagery and ethnocultural identities in contemporary multicultural women writing in Canada - Hinnerová, Katarína, 1983- (2007)
The thesis focuses on food imagery as an efficient means of conveying contemporary discourse on ethnocultural identities which is tending towards transcultural perspectives, and it highlights food’s potential to establish the awareness of diversity, challenge exclusionary attitudes and stimulate cross-cultural interaction. Observations and conclusions are based on the analysis of Hiromi Goto’s Chorus of Mushrooms, which is set in the context of Canadian sociocultural milieu, and also in the context of "food" writing of several other contemporary multicultural women writers of Canada.